Lewis Acid Guests in a P8W48 Archetypal Polyoxotungstate Host: Enhanced Proton Conductivity via Metal‐Oxo Cluster within Cluster Assemblies. Issue 40 (30th July 2018) - Yang, Peng; Alsufyani, Maryam; Emwas, Abdul‐Hamid; Chen, Chaoqin; Khashab, Niveen M.
Abstract: Complexes made by hosts that completely surround their guests provide a means to stabilize reactive chemical intermediates, transfer biologically active cargo to a diseased cell, and construct molecular‐scale devices. By the virtue of inorganic host–guest self‐assembly, nucleation processes in the cavity of a P8 W48 ‐archetype phosphotungstate has afforded a nanoscale 16‐Al III ‐32‐oxo cluster and its Ga III analogue that contain the largest number of Al III /Ga III ions yet found in polyoxometalate (POM) chemistry. Interestingly, the rich Lewis acid Al III centers within the Lewis base POM support shows an exceptional proton conductivity of 4.5×10 −2 S cm −1 (85 °C, 70 % RH; RH: relative humidity), which is by far the highest conductivity reported among POM‐based single‐crystal proton conductors. Abstract : Guest house : Host–guest self‐assembly of the wheel‐shaped P8 W48 phosphotungstate with strong Lewis acid centers resulted in polyoxometalates (POMs) containing the largest Al III ‐oxo and Ga III ‐oxo clusters. The enhanced proton conductivity of the Al III derivative arises from the synergistic effect imposed by the rich Lewis acid–base pairs as well as acidic nitrate functions.